2015
DOI: 10.4212/cjhp.v68i5.1483
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Dabigatran for Atrial Fibrillation at 3 Tertiary Care Centres

Abstract: Background:The outpatient management of stroke prevention for patients with atrial fibrillation has recently been published and provides insight into the benefits and risks of the new direct-acting oral anticoagulants. However, real-world use of these agents for hospital inpatients requires additional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Both drugs have a potential to increase the bleeding risk. A previous study found that approximately 7% of dabigatran users were concomitantly receiving low molecular weight heparin [22]. Thus, a medication monitoring system to detect such contraindicated combinations is warranted to reduce the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Both drugs have a potential to increase the bleeding risk. A previous study found that approximately 7% of dabigatran users were concomitantly receiving low molecular weight heparin [22]. Thus, a medication monitoring system to detect such contraindicated combinations is warranted to reduce the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-seven percent of patients had potential interactions, which is just below the lower limit of the range collated from other studies with DOACs in clinical settings (40-88%). [28][29][30][31][32][33][34] Twice as many patients had potential PD-DDIs with DOACs compared with PK-DDIs, driven predominantly by concomitant use of SSRIs/SNRIs [ Figure 1(a, b)].…”
Section: Discussionmentioning
confidence: 99%
“…Third, apixaban, rivaroxaban and dabigatran were studied here, whereas most of the comparator studies included only dabigatran. [28][29][30][31][32][33][34] The prevalence difference could be explained because PPIs were classified as interacting drugs in several of the previous dabigatran studies, in which up to 64% of patients were taking dabigatran and PPIs together. 32 The rationale for this classification is that the bioavailability of dabigatran is dependent on an acidic gastric environment, and pantoprazole decreased dabigatran absorption by 30% in a phase I healthy volunteer study and by an average of 12.5% in RE-LY.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations